Peak - Smith, Roland, 1951- (Orlando, Fla. : Harcourt, 2007)
A fourteen-year-old boy attempts to be the youngest person to reach the top of Mount Everest.
Booklist starred.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Mountaineering -- Juvenile fiction; Coming of age -- Fiction; Mountaineering -- Fiction; Survival -- Fiction; Bildungsromans; Mountaineering -- Fiction; Survival skills -- Fiction; Everest, Mount (China and Nepal) -- Juvenile fiction; Everest, Mount (China and Nepal) -- Fiction; Everest, Mount (China and Nepal) -- Fiction